Penerapan Pembelajaran Membaca, Menulis dan Berhitung (CALISTUNG) dan Literasi dalam Bimbingan Belajar Gratis di SDN 094135 Tigabolon - Yanti Kristina Sinaga; Muktar B. Panjaitan; Rosma Simangunsong; Saratahoma Sidabutar; Pirngadita Purba; Masniawita Gloria Sinaga; Yanta Damanik; Steven Yuki Damanik (Utan Kayu Publishing, 2022)
Community service activity (PkM) is carried out by students of the HKBP Nommensen University Medan at SD Negeri 094135 Tigabolon. The PkM participants consist of four students who are guided by a field supervisor (DPL) assigned by the Universitas HKBP Nommensen in Medan. This PkM is carried out within one month from 02 to 28 February 2022. This PkM is carried out as an implementation of the MBKM curriculum which is being implemented in various public and private campuses throughout Indonesia. Universitas HKBP Nommensen takes part in improving the quality of education in North Sumatra and Riau through this PkM program. This PkM is carried out outside of students' school hours with the aim of helping to optimize students' abilities at SDN 094135 Tigabolon and solve the difficulties faced by students. This PkM is held every Monday-Thursday at 13.00-15.00 WIB. This technical implementation is based on the instructions of the principal and the needs of students. This PkM is carried out by students evenly to students starting from grade one to grade six. Based on the sharing session activities carried out by DPL with PkM participating students, the PkM implementation can run well. The school accepts it well and can coordinate with all teachers in the school, including the education staff. The presence of this PkM has a positive impact on students at SD Negeri 094135 Tigabolon. Learning problems experienced by students can be resolved properly, especially in reading, writing, arithmetic, and understanding literacy well. This can be seen from the benchmark of the ability of students before the implementation of this PkM program. The school is willing to accept the next PkM participants because it has a positive impact on the school.